Sate of the system Mobile.
The GamePros share what's keeping them busy on their iPhones and what's keeping their devices in pockets.
Keywords: iPhone (Smartphone); Solitaire (Game); Catle Smasher; Game Dev Story; Cut the Rope; Plants vs. Zombies; Angry Birds